The Views of Classroom Teachers on Project Tasks - KÖĞCE, Davut; ASLANDAĞ, Buket (Asian Journal of Education and Training, 2018)
This study was conducted in order to determine the opinions of the class teachers regarding the project tasks. For this purpose, semi-structured interviews were conducted with 47 classroom teachers. The obtained data were subjected to content analysis using the MAXQDA 11 and "coding of the data" technique was used in the data analysis techniques. Consequently, it was concluded that the main purpose of classroom teachers in providing students with project skills is to develop research skills of students, to demonstrate creativity skills of the pupils, to make them use the knowledge and skills they have and enable them to produce an output. criteria that project tasks consider when evaluating are direct factors such as student activity and written exam success, and indirect factors such as adherence to the project schedule, and cleanliness, rigor and discipline of the project.